Red rising [large type] - Brown, Pierce, 1988- (Brown, Pierce, 1988- Red rising saga, 2014)
A tale set in a bleak future society torn by class divisions follows the experiences of secret revolutionary Darrow, who after witnessing his wife's execution by an oppressive government joins a revolutionary cell and attempts to infiltrate an elite military academy.